Production de l’information météorologique et climatique au Sénégal - CGIAR Research Program on Climate Change, Agriculture and Food Security; International Crops Research Institute for the Semi-Arid Tropics; United States Agency for International Development; Agence Nationale de l'Aviation Civile et de la Météorologie (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Production de l’information météorologique et climatique au Sénégal